Experiments and calibration of a bond-slip relation and efficiency factors for textile reinforcement in concrete. (November 2022) - Sciegaj, Adam; Larsson, Fredrik; Lundgren, Karin
Abstract: Textile reinforcement yarns consist of many filaments, which can slip relative each other. At modelling of the global structural behaviour, interfilament slip in the yarns, and slip between the yarns and the concrete can be considered by efficiency factors for the stiffness and strength of the yarns, and by applying a bond-slip relation between yarns and concrete. In this work, an effective and robust method for calibration of such models was developed. Two-sided asymmetrical pull-out tests were carried out, with varying embedment lengths designed to obtain both pull-out and rupture of the textile as failure mode. The efficiency factors for strength and stiffness of the textile were very similar, 34% and 35% respectively. This indicates the stress distribution within a yarn to be uneven in a similar manner for small and large stress levels, and that interfilament slip has a larger influence than variation of filaments' strength. Highlights: Robust calibration of bond-slip and efficiency factors for textile yarns in concrete. Pull-out tests with varying embedment lengths resulting in pull-out and rupture. Indirect calibration procedure combined with finite element analyses. Similar efficiency factors for strength and stiffness of the carbon textile yarn. Interfilament slip appearing more influential than variation of filaments' strength.